Tuning the Mind: Connecting Aesthetics to Cognitive Science - Katz, Ruth; HaCohen, Ruth (New Brunswick Transaction, 2003)
Starting from the late Renaissance, efforts to make vocal music more expressive heightened the power of words, which, in turn, gave birth to the modern semantics of musical expression. As the skepticism of seventeenth-century science divorced the acoustic properties from the metaphysical qualities of music, the door was opened to dicern the rich links between musical perception and varied mental faculties. In Tuning the Mind, Ruth Katz and Ruth HaCohen trace how eighteenth century theoreticians of music examined anew the role of the arts within a general theory of knowledge.As the authors note, the differences between the physical and emotional dimensions of music stimulated novel conceptions and empirical inquiries into the old aesthetic queries. Tracing this development, their opening chapter deals with seventeenth-century epistemological issues concerning the artistic qualities of music. Katz and HaCohen show that painting and literature displayed a comparable tendency toward "musicalization," whereby the dynamic of forms-the modalities specific to each artistic medium-rather than subject matter was believed to determine expression. Katz and HaCohen explore the ambiguities inherent in idealization of an art form whose mimetic function has always been problematic. They discuss the major outlines of this development, from Descartes to Vico through Condillac. Particular emphasis is placed on eighteenth-century British thinkers, from Shaftesbury to Adam Smith, who perceived these problems in their full complexity. They also explore how the French and the Germans dealt differently with questions that preoccupied the British, each nation in accordance with their own past tradition and tendencies. The concluding chapter summarizes the parallel development of abstract art and basic hypotheses concerning the mind and explores basic theoretical questions pertaining to the relationship between perception and cognition.In addressing some of the most complex problems in musical aesthetics, Katz and HaCohen provide a unique historical perspective on the ways their art creates and develops coherent worlds, and, in so doing, contribute to our understanding of the workings of the mind.
Keywords: Esthetics; Natural science; Psychology